Efficiency of Electron Transfer Initiated Chemiluminescence1. (22nd July 2013) - Augusto, Felipe A.; de Souza, Glalci A.; de Souza Júnior, Sergio P.; Khalid, Muhammad; Baader, Wilhelm J.
Abstract: Although the mechanisms of many chemiluminescence (CL) reactions have been intensively studied, no general model has been suggested to rationalize the efficiency of these transformations. To contribute to this task, we report here quantum yields for some well‐characterized CL reactions, concentrating on recent reports of efficient transformations. Initially, a short review on the most important general CL mechanisms is given, including unimolecular peroxide decomposition, electrogenerated CL, as well as the intermolecular and intramolecular catalyzed decomposition of peroxides. Thereafter, quantum yield values for several CL transformations are compiled, including the unimolecular decomposition of 1, 2‐dioxetanes and 1, 2‐dioxetanones, the catalyzed decomposition of appropriate peroxides and the induced decomposition of properly substituted 1, 2‐dioxetane derivatives. Finally, some representative examples of quantum yields for complex CL transformations, like luminol oxidation and the peroxyoxalate reaction, in different experimental conditions are given. This quantum yield compilation indicates that CL transformations involving electron transfer steps can occur with high efficiency in general only if the electron transfer is of intramolecular nature, with the intermolecular processes being commonly inefficient. A notable exception to this general rule is the peroxyoxalate reaction which, also constituting an example of an intermolecular electron transfer system, possesses very high quantum yields. Abstract : Quantum yields are reported for several important chemiluminescence reactions, which involve electron transfer processes in the chemiexcitation step. Quantum yields are high for intramolecular transformations whereas they are very low for most intermolecular processes, with the notable exception of the peroxyoxalate reaction.